A new glacial isostatic adjustment model for Antarctica: calibrated and tested using observations of relative sea-level change and present-day uplift rates - Whitehouse, PL; Bentley, MJ; Milne, GA; King, MA; Thomas, ID (Geophysical Journal International, 2012)
We present a glacial isostatic adjustment (GIA) model for Antarctica. This is driven by anew deglaciation history that has been developed using a numerical ice-sheet model, and isconstrained to fit observations of past ice extent. We test the sensitivity of the GIA model touncertainties in the deglaciation history, and seek earth model parameters that minimize themisfit of model predictions to relative sea-level observations from Antarctica. We find thatthe relative sea-level predictions are fairly insensitive to changes in lithospheric thickness andlower mantle viscosity, but show high sensitivity to changes in upper mantle viscosity andconstrain this value (95 per cent confidence) to lie in the range 0.82.0 10 21 Pa s. Significantmisfits at several sites may be due to errors in the deglaciation history, or unmodelled effects oflateral variations in Earth structure. When we compare our GIA model predictions with elastic correctedGPS uplift rates we find that the predicted rates are biased high (weighted meanbias = 1.8mm yr 1 ) and there is a weighted root-mean-square (WRMS) error of 2.9mm yr 1 .In particular, our model systematically over-predicts uplift rates in the Antarctica Peninsula,and we attempt to address this by adjusting the Late Holocene loading history in this region,within the bounds of uncertainty of the deglaciation model. Using this adjusted model theweighted mean bias improves from 1.8 to 1.2mm yr 1 , and the WRMS error is reduced to2.3mm yr 1 , compared with 4.9mm yr 1 for ICE-5G v1.2 and 5.0mm yr 1 for IJ05. Finally,we place spatially variable error bars on our GIA uplift rate predictions, taking into accountuncertainties in both the deglaciation history and modelled Earth viscosity structure. Thiswork provides a new GIA correction for the GRACE data in Antarctica, thus permitting moreaccurate constraints to be placed on current ice-mass change.